A STUDY ON THE PROBLEM OF SPEAKING ANXIETY OF THE SECOND YEAR STUDENTS OF SMK YAPIM TAMBUSAI UTARA - Sri Rahmadani; Supriusman Supriusman; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: English as a foreign language is one of the languages that should be required by Indonesian students through learning speaking. However, it is found that they have anxiety while speaking. This research aims to find out students’ anxiety in speaking. This is descriptive research. It was conducted at a Vocational High School, especially in the XI TKJ (Computer and Network Engineering) class of Second-Year Students. In collecting the data, the researcher used questionnaire by Horwitz (1986). The results of the data showed that the highest speaking anxiety level was in communication apprehension with a mean score of 3.22. So, the speaking anxiety level of the second-year students of (Vocational High School) YAPIM Tambusai Utara was mediocre. Besides, the lowest level was in fear of negative evaluation aspects with a mean score of 3.17.Key Words: Study, Problem, Speaking, the Anxiety, the Speaking Anxiety.